Network System Planning of Wastewater Treatment Plant (WWTP) at Ternater Fishing Port TPI to Improve Environmental Quality - Rais D. Hi Yusuf; Sudarman Jainal (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Fishing activities that occur in this market produce waste water that still contains pollutants with concentrations above quality standards. This causes the waste water to smell bad and have high turbidity. Planning a liquid waste processing system in a market is needed to improve the quality of the air that will be discharged so that it does not pollute the environment. This research is about planning a Waste Water Treatment Plant (IPAL) network system at the fish marketing site at the Ternate fishing port. From this research, we will know the design of the Waste Water Treatment Plant System and also the Cost Budget Plan (RAB) for the planning of the IPAL. From the results of the analysis of waste water discharge calculations at the Ternate fisheries market with a total of 40 selling table units producing waste water, namely, 3,333 liters/day. So an IPAL can be designed with a length of 6.1 m, a width of 1.8 m and a height of 1.65 m. The planning for the Fishery Market Wastewater Treatment Plant has 6 compartments, namely, Screen tank or Oil/Fat Separator Tank which has a volume of 0.16 m3/day => Equalization tank has a volume of 1.4 m3/day => Initial sedimentation tank has a volume of 1 .2 m3/day => Anaerobic Biofilter tank has a volume of 1.1 m3/day => Aerobic Biofilter tank has a volume of 1.4 m3/day => Final settling tank has a volume of 0.18 m3/day. The budget required for implementing the planning for the Waste Water Treatment Plant (IPAL) at the Fisheries Market is IDR. 86,009,000.00.